Economic and Environmental Benefits of Eliminating Log Export Bans-The Case of Costa Rica - Kishor, Nalin; Constantino, Luis.; Mani, Muthukumara (Washington, D.C. : International Monetary Fund, 2001)
An increasing number of tropical timber producing nations have enacted bans on export of logs. Proponents argue that a log export ban is a second-best policy tool for addressing environmental externalities; it also creates more jobs and improves scale efficiencies domestically. Theoretical arguments suggest that log export bans are largely incapable of achieving their objectives. However, little quantitative evidence exists. The authors maintain that eliminating log export bans in Costa Rica could generate economic gains as high as USD 14 million annually in addition to the environmental benefits.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet